The Influence of Implementation of Risk-Based Audit and Utilization of Information Technology on Tax Audit Quality - Maulana, Fajar; Devano, Sony; Harahap, Devianti Yunita (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The low quality of tax audits is one of the sources of tax disputes. Therefore, tax audit actions should be carried out optimally, effectively, efficiently, and with high quality. The purpose of this research is to determine the influence of the implementation of risk-based audit and the utilization of information technology on the quality of tax audits. The research method used in this study is a quantitative approach with a descriptive method through a survey conducted by distributing questionnaires to the respondents, the Heads of Tax Offices (KPP), in Jakarta and West Java regions, as well as the Middle Taxpayers Offices (KPP Madya) throughout Indonesia. The research obtained a sample of 44 respondents. The data analysis technique used is Multiple Linear Regression analysis with the assistance of SPSS Version 23 software. The results of this study indicate that the implementation of risk-based audit has a positive effect on the quality of tax audits. The utilization of information technology also has a positive effect on the quality of tax audits. Simultaneously, the implementation of risk-based audit and the utilization of information technology affect the quality of tax audits.